1994
DOI: 10.1136/thx.49.5.468
|View full text |Cite
|
Sign up to set email alerts
|

Relation of lung function, maximal inspiratory pressure, dyspnoea, and quality of life with exercise capacity in patients with chronic obstructive pulmonary disease.

Abstract: Background -Several studies have shown that both objective and subjective measurements are related to exercise capacity in patients with chronic obstructive pulmonary disease (COPD) (Thorax 1994;49:468-472) Patients with chronic obstructive pulmonary disease (COPD) usually have a decreased exercise tolerance and a reduced quality of life. While spirometric measurements seem to be related to maximum ventilation in a bicycle ergometer performance,' in general they correlate weakly with less stressful tests s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

27
100
4
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(140 citation statements)
references
References 19 publications
27
100
4
8
Order By: Relevance
“…It was suggested that the six-minute walk test can be used instead of a spirometer to determine the severity of COPD (12). Studies investigating the correlation of the six-minute walk test with spirometric parameters demonstrated significant correlations with FEV 1 (31) and DLCO (35,36). In the present study, the six-minute walk test showed a positive correlation with FEV 1 (%), FEV 1 /FVC, and DLCO (%) values.…”
Section: Discussionsupporting
confidence: 66%
“…It was suggested that the six-minute walk test can be used instead of a spirometer to determine the severity of COPD (12). Studies investigating the correlation of the six-minute walk test with spirometric parameters demonstrated significant correlations with FEV 1 (31) and DLCO (35,36). In the present study, the six-minute walk test showed a positive correlation with FEV 1 (%), FEV 1 /FVC, and DLCO (%) values.…”
Section: Discussionsupporting
confidence: 66%
“…This result may be explained by the fact that the group was submitted to an intervention protocol that result in improvement of pulmonary rexpansion and of ventilatory pattern and could reduce sensation of dyspnea and perceived effort in these patients. It is demonstrated that the functional limitations correlate positively to the roamed distance and to dyspnea reporter during 6MWT 25 . Conversely, studies that assessed the sensation of effort and dyspnea perceived during 6MWT after cardiac surgery demonstrated that the effort sensation may be related to psychological aspects and to the performance during 6MWT.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise intolerance is one of the important aspects of health related quality of life in COPD (19,20) and there is considerable evidences that pulmonary rehabilitation programs improve exercise tolerance and patients' health related quality of life (21,22). There is little evidence about the relationship between subjective complaints in COPD and objective parameters.…”
Section: Discussionmentioning
confidence: 99%